Serological Detection of Parvovirus B19 in Thalassemia Patients in Thi Qar City - Shaheed Sami Dayekh; Biologist Hameed Kameel Fanos (American Journal of Biology and Natural Sciences, 2024)
The parvovirus B-19 is a tiny, unwrapped, single-strand DNA virus which has an icosahedral capsid of 18–26 nm. A blood transfusion and airborne droplets can spread and induce a variety of illnesses, including fetal hydrops, arthropathy, contagious erythema, and transient aplastic crises. Through the serological detection of particular anti-Parvovirus B19 IgM and IgG in the patients’ sera, this case control research seeks to identify Parvovirus B19 in the pathophysiology and complications of beta thalassemia major. 120 patients each had blood samples taken for serology in order to identify a particular anti-Parvovirus B19 antibody using ELISA. In contrast to a control group that had negative findings for both IgM and IgG, the serological data showed that 2 (1.7%) and 37 (30.8%) of the beta thalassemia major were positive for IgM and IgG antibodies specific for Parvovirus B19, respectively. According to statistical analysis, there was no significant difference (P=0.497) in the detection of anti-Parvovirus B19 IgM antibody between the patients and control, however there was a large significant difference (P<0.001) regarding anti-Parvovirus B19 IgG antibody. In conclusion, the identification of antibodies in thalassemia patients may suggest that this virus contributes to thalassemia patients’ exacerbations.